2022
DOI: 10.3171/case22157
|View full text |Cite
|
Sign up to set email alerts
|

Primary spinal infections in patients with solid organ transplant: a systematic literature review and illustrative case

Abstract: BACKGROUND Primary spinal infections (PSIs) are a group of uncommon but serious infectious diseases considered more prevalent and aggressive among patients with chronic immunocompromised states. Association of PSI and solid organ transplant has not been systematically analyzed. The authors performed a systematic review analyzing clinical presentation and mortality of patients with PSI in the setting of solid organ transplant. OBSERVATIONS PSIs in patients with immunosuppressive therapy, such as those with so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Close monitoring of their condition by their primary oncologists may explain why the diagnosis of PSI in this population was on average faster (29.3 days) compared with the 2 to 6 months’ delay observed by Waheed et al or with the 49.9 days’ delay observed by Pola et al 18 , 19 It is important to highlight that the lag time in diagnosis is correlated with higher rates of mortality and complications. 1 - 3 However, when considering that the extent of infection can be used as a proxy for severity of symptoms and the need for surgical intervention, the immunosuppressed state of this patient population may contribute to the higher number of patients who underwent surgery. In our cohort, 48.3% patients required surgery (14 of 29 patients) while Pola et al 20 reported that 22.75% (47 of 207 patients) of their cohort required surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Close monitoring of their condition by their primary oncologists may explain why the diagnosis of PSI in this population was on average faster (29.3 days) compared with the 2 to 6 months’ delay observed by Waheed et al or with the 49.9 days’ delay observed by Pola et al 18 , 19 It is important to highlight that the lag time in diagnosis is correlated with higher rates of mortality and complications. 1 - 3 However, when considering that the extent of infection can be used as a proxy for severity of symptoms and the need for surgical intervention, the immunosuppressed state of this patient population may contribute to the higher number of patients who underwent surgery. In our cohort, 48.3% patients required surgery (14 of 29 patients) while Pola et al 20 reported that 22.75% (47 of 207 patients) of their cohort required surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions include intravenous or oral antibiotics and more invasive surgical methods, such as abscess drainage or decompressive laminectomy for extensive infections. 1 - 3 …”
mentioning
confidence: 99%
See 1 more Smart Citation